دراسة عددية لمشكلة التداخل بين أساسين شريطيين متجاورين يستندان على تربة رملية - صفوان عبدالله; توفيق فياض; آمنة سلمان (Tishreen University, 2019)
تم في هذا البحث دراسة تأثير تداخل أساسين شريطيين متجاورين يستندان على تربة رملية في قدرة تحمل وهبوط كل منهما باستخدام طريقة العناصر المحدودةFEM وفق برنامجPLAXIS 2D, تمت الدراسة من أجل ثلاثة أنواع من الترب الرملية ( مخلخلة , متوسطة الكثافة , كثيفة ) , وتم التركيز في دراستنا على التربة الرملية متوسطة الكثافة , واجراء دراسة بارامترية لبعض أهم العوامل المؤثرة في قيم قدرة التحمل والهبوط (زاوية الاحتكاك الداخلية ø ، عمق منسوب التأسيس Df ). حيث لاحظنا أن كل من قدرة التحمل والهبوط النهائيين لحالة الأساسين الشريطيين المتداخلين تزداد مع نقصان المسافة بينهماS حتى يصلا إلى قيمة أعظمية والتي تقابل مسافة حرجة بين الأساسين المتداخلين Scr بعدها يتناقص كل من قدرة التحمل والهبوط النهائيين مع الاستمرار في تناقص المسافة بينهما حتى يحصل تماس بين الأساسين, ووجدنا بأن تأثير التداخل يزداد ويصبح أوضح مع زيادة كل من زاوية الاحتكاك الداخلية وعمق منسوب التأسيس, كما لاحظنا بأن المسافة التي يصبح عندها تأثير التداخل مهملاً Smax تزداد مع زيادة الكثافة النسبية وزاوية الاحتكاك الداخلية للتربة الرملية. وبمقارنة النتائج التي حصلنا عليها مع نتائج الدراسات السابقة وجدنا أنها كانت على توافق جيد معها. In this paper,the effect of the interference on bearing capacity and settlement of two adjacent strip footings resting on sandy soil is studied by using finite element method, (FEM program PLAXIS 2D). The study was conducted for three types of sandy soils (loose, medium density, dense), in our study we focused on the sandy soil medium density ,Then a parametric study of some of the most important factors that affecting on the values of bearing capacity and settlement(the properties of sand Dr%, foundation depth Df) is performed. We observed that both of the bearing capacity and settlement of interfering strip footings increase with a decrease in the spacing between footing S, until it reaches a maximum value corresponding to a certain critical spacing between the footings Scr , then ultimate bearing capacity and settlement decrease with decrease in the spacing until the two adjacent footings contact. We also found that the effect of interference increases and becames clearer with an increase in the relative density Dr% and the internal friction angle Ø.We also noticed that the distance at which the interference effect becomes negligible Smax increases with the increase in relative density and internal friction angle. By comparing the results obtained from this study with the results of the previous studies, we found that they are in  a good agreement with them.